2013
DOI: 10.1371/journal.pone.0058500
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Regulation of Connexin43 in H-Ras-Transformed Cells

Abstract: Connexin43 (Cx43) expression is lost in cancer cells and many studies have reported that Cx43 is a tumor suppressor gene. Paradoxically, in a cellular NIH3T3 model, we have previously shown that Ha-Ras-mediated oncogenic transformation results in increased Cx43 expression. Although the examination of transcriptional regulation revealed essential regulatory elements, it could not solve this paradox. Here we studied post-transcriptional regulation of Cx43 expression in cancer using the same model in search of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The downreguation of cyclin-dependent kinase 6 by miRNA-124-3p transferred between glioblastoma cells via gap junctions promotes the anti-proliferative effect [ 71 ]. The different mechanism involving post-transcriptional regulation of Cx43 is recently reported in H-Ras-transformed cells compared to non-transformed parental cells; 5′untranslated region (UTR) is active in Ras-transferred NIH-3 T3 cells while the 3′UTR is active in normal, non-transformed NIH-3 T3 cell and a regulatory element in the 3′UTR was identified [ 72 ]. This study suggests specific regulatory mechanisms in regulation of connexin expression in cancer cells.…”
Section: Connexin Channels In Cell Cycle Progression Cell Proliferatmentioning
confidence: 99%
“…The downreguation of cyclin-dependent kinase 6 by miRNA-124-3p transferred between glioblastoma cells via gap junctions promotes the anti-proliferative effect [ 71 ]. The different mechanism involving post-transcriptional regulation of Cx43 is recently reported in H-Ras-transformed cells compared to non-transformed parental cells; 5′untranslated region (UTR) is active in Ras-transferred NIH-3 T3 cells while the 3′UTR is active in normal, non-transformed NIH-3 T3 cell and a regulatory element in the 3′UTR was identified [ 72 ]. This study suggests specific regulatory mechanisms in regulation of connexin expression in cancer cells.…”
Section: Connexin Channels In Cell Cycle Progression Cell Proliferatmentioning
confidence: 99%
“…Besides having junctional properties, Cx43 is also an important player in regulating cell growth and differentiation (Araya et al, 2005), with an established tumor suppressive properties (Kandouz et al, 2013).…”
mentioning
confidence: 99%
“…Previously we examined another mutation in this same domain (D3N) and found that human fibroblasts exhibited a lower expression of Cx43 and impaired Cx43 function ( Churko et al ., 2011b ; Esseltine et al ., 2015 ). Of interest, both D3N and L7V mutants are located in the N-terminal domain, and both mutants lead to reduced Cx43 RNA levels, which suggests that this part of the sequence is important for Cx43 RNA transcription and/or stability and may be affected by important regulatory elements ( Kandouz et al ., 2013 ; Oyamada et al ., 2013 ). L7V-expressing fibroblasts can deliver low levels of Cx43 to the cell surface, where they may contribute to increased (“leaky”) ATP release and form few gap junction channels.…”
Section: Discussionmentioning
confidence: 99%